O gerenciamento da cadeia de suprimentos em megaeventos - Hora, Isabella Mayara Abreu da (2019)
Mega-events are considered a grandiose manifestation capable of impacting the organization and planning of the host city, leaving unimaginable legacies and lessons learned for future events. In this context, freight transportation is a critical function guaranteeing event resources. The municipality of Rio de Janeiro has been hosted the last mega-sports event venue in Brazil. The Olympic Games held in Rio in 2016 serves as the object of this study because of the detailed coordination of a complex operation involving people, facilities, and supplies was the aggregation of all the mega-events experienced in Brazil two decades. The aim of this work is to present a set of good practices for the coordination of supply chain management in mega-events. Bibliographical and documentary researches as well as interviews were carried out with the aim of learning from the experts and sponsors. This was an analysis of the complexity of the activity where resulting data may contribute to the successful accomplishment of future events. The originality of this work is to fill in some of the missing gaps in the current literature used to strategize large events that have enormous social and economic consequences years after. One of the contributions is a characterization of the transported loads and the identification of the supply chain in mega-events.